The Impact of Social Media Marketing on Consumer Buying Behavior among Millennials - A. Balasubramanian (International Journal of Advanced Science and Technology, 2019)
This study investigates the influence of social media marketing on the purchasing behaviors of millennials. Social media has become a powerful tool in shaping consumer decisions, particularly among younger generations who are constantly connected online. Through a combination of primary and secondary research, the study examines how social media channels like Facebook, Instagram, and YouTube affect the buying patterns of millennials. The findings highlight the critical role that social media plays in modern marketing strategies and its effectiveness in reaching and influencing this demographic.